2020
DOI: 10.21203/rs.3.rs-41035/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The symbiotic capacity of rhizobium shapes root-associated microbiomes

Abstract: Background: Root-microbiome interactions are of central importance for plant performance and yield. A distinctive feature of legumes in this context is that they engage in symbiosis with rhizobia, which are abundant in soils and include both symbiotic and non-symbiotic bacterial strains. If and how the capacity of rhizobia to form symbiosis modulates root-associated microbiomes are not well understood. Results: We address this question by inoculating soybean (Glycine max) plants with wild type (WT) or a noeI m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
(115 reference statements)
1
5
0
Order By: Relevance
“…In this study, we treated soil with saponins that had either steroid- or oleanane-type aglycones. The bacterial α-diversity was found to decrease with all four saponin treatments, which was consistent with previous results for benzoxazolin-2(3H)-one (BOA), quercetin, daidzein, flavonoid mixture, α-tomatine, and tomatidine [ 20 , 22 , 37 , 47 ]. The decreases found in the bacterial α-diversity were in accordance with previous observations made for the rhizosphere when affected by root exudates [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, we treated soil with saponins that had either steroid- or oleanane-type aglycones. The bacterial α-diversity was found to decrease with all four saponin treatments, which was consistent with previous results for benzoxazolin-2(3H)-one (BOA), quercetin, daidzein, flavonoid mixture, α-tomatine, and tomatidine [ 20 , 22 , 37 , 47 ]. The decreases found in the bacterial α-diversity were in accordance with previous observations made for the rhizosphere when affected by root exudates [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Treating soil with pure compounds has revealed the strong influences PSMs have in shaping the microbiota [ 19 , 20 , 21 , 22 , 35 , 37 , 47 ]. In this study, we treated soil with saponins that had either steroid- or oleanane-type aglycones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For fungi, Bradyrhizobium japonicum 5038 inoculation in the soybean also facilitated an increase in the number of connections between fungi, including the hub fungi shift to Phaeosphaeria, Sporobolomyces, Septoria, Edenia, and Leptospora (Xu et al, 2020). Moreover, by building mutants with a defective Nod factor, previous research confirmed that the symbiosis compromised NoeI mutant-inoculation could reduce microbial diversity and co-occurrence interactions, and decrease the abundance of beneficial microbes (Liu et al, 2020). This could be because the inoculated Bradyrhizobium japonicum 5038 forms a more symbiotic system with the host plant, which was changed by altering plant root exudates such as flavonoid (White et al, 2015), Catechin (Mommer et al, 2016), and some volatile organic compounds to change the soil physical and chemical environment and influence the prevalence of rhizosphere microorganisms (Vishwakarma et al, 2020).…”
Section: Co-inoculation Of Bradyrhizobium Japonicum 5038 and Bacillus...mentioning
confidence: 87%